USING STYLISTIC DEVICES IN ENGLISH LANGUAGE COMPARED WITH UZBEK LANGUAGE (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article delves into the nuanced world of stylistic devices, examining their usage in both English and Uzbek languages. By juxtaposing these two linguistic frameworks, the study aims to shed light on the diverse array of techniques employed to convey meaning, evoke emotions, and captivate audiences in each language. Through a comprehensive analysis of various stylistic devices such as metaphors, similes, alliteration. The article highlights similarities, differences, and cultural implications inherent in their application. Additionally, the article discusses the impact of linguistic and cultural contexts on the effectiveness and interpretation of stylistic devices in both languages, providing valuable insights for language learners, educators and researchers alike.